2013
DOI: 10.1007/s00330-013-2958-z
|View full text |Cite
|
Sign up to set email alerts
|

Computed diffusion-weighted imaging using 3-T magnetic resonance imaging for prostate cancer diagnosis

Abstract: cDWI2000 appears to be more effective than mDWI1000, and at least as effective as mDWI2000 for PCa diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 19 publications
3
66
0
Order By: Relevance
“…For instance, one study showed the superiority of acquired b=2000s/mm 2 DWI compared to b=1000s/mm 2 DWI [31]. We also found better lesion visibility at b=2000s/mm 2 (72%) compared to b=1000s/mm 2 DWI (55%).…”
Section: Discussionsupporting
confidence: 54%
“…For instance, one study showed the superiority of acquired b=2000s/mm 2 DWI compared to b=1000s/mm 2 DWI [31]. We also found better lesion visibility at b=2000s/mm 2 (72%) compared to b=1000s/mm 2 DWI (55%).…”
Section: Discussionsupporting
confidence: 54%
“…Another study reported the best diagnostic performance for prostate tumor detection when T2 weighted images were evaluated in conjunction with b2000 DWI, regardless of whether a set of “measured” or “calculated” b2000 images were used. 87 …”
Section: Advances In Prostate Diffusion-weighted Imagingmentioning
confidence: 99%
“…. 13 However, it remains unclear which combination of b-values is optimal for generating cDWI with a high b-value such as 2000 s mm 22 for detection of PCa in routine clinical practice. The aim of our study was therefore to evaluate the influence of the combinations of b-values on cDWI at b 5 2000 s mm 22 for PCa detection and to determine the optimal combination on a 3-T MR system.…”
Section: -12mentioning
confidence: 99%
“…This finding agrees with the results of previously reported studies. [10][11][12][13] Blackledge et al 10 performed a copper sulfate phantom study and found that the noise remains constant across b-values for acquired images, whereas for computed images, it decreases when the b-value increases to .840 s mm 22 . Computed DWI images are thus more likely than acquired images to highlight differences in SI between cancerous and non-cancerous tissue on images with high b-values.…”
Section: Full Paper: Computed Diffusion-weighted Mri For Prostate Canmentioning
confidence: 99%